Political economy of tobacco control in Thailand. Issue 1 (1st March 2001) - Chantornvong, Sombat; McCargo, Duncan
Abstract : Thailand has some of the world's strongest anti-tobacco legislation. This paper examines the political economy of tobacco control in Thailand, emphasising the identification of forces which have supported and opposed the passage of strong anti-tobacco measures. It argues that while a powerful tobacco control coalition was created in the late 1980s, the gains won by this coalition are now under threat from systematic attempts by transnational tobacco companies to strengthen their share of the Thai cigarette market. The possible privatisation of the Thailand Tobacco Monopoly could threaten the tobacco control cause, but the pro-control alliance is fighting back with a proposed Health Promotion Act which would challenge the tobacco industry with a hypothecated excise tax dedicated to health awareness campaigns.